Analisis Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kota Medan - Naimah Mardhiah Matondang; Isnaini Isnaini; Warjio Warjio (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Based on the results of the performance appraisal of civil servants at the Medan City Population and Civil Registration Office in 2020 and 2021, it shows that employee performance has decreased, and there are employee discipline issues that need to be corrected. So the formulation of the problem in this study is how is the performance of employees at the Department of Population and Civil Registration of the City of Medan and what factors are hindering the performance of employees at the Office of Population and Civil Registration of the City of Medan. The research method used in this research is descriptive with qualitative analysis. Sources of data obtained from interviews, documentation, and observation. With the results of the study that the performance of Medan City Disdukcapil employees in population administration services is still relatively poor. Performance indicators according to Mangkunegara theory that have not been implemented properly are the quantity of work, work discipline and work initiatives. While the indicators of work quality and responsibility have been carried out properly by employees. While the recommendation in this study is that Medan City Disdukcapil employees need to be more aware of the importance of working time discipline, so that employees work at all predetermined working hours. Leaders need to be more assertive in disciplining employees who violate work time regulations so that they can provide good learning for all employees. Employees should seek efforts to speed up the handling of population administration work without compromising quality or accuracy in carrying out work. It is better if the leader needs to exercise better supervision of his subordinates so that there is no opportunity to abuse the authority given to him.